The Reconstruction of Subjectum Litis in Term of Reflections on Constitutional Dissolution of Political Parties - I Gede Agus Kurniawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This legal research aims to examine the awarding of political parties currently in force in Indonesia through the Constitutional Court and provide a conclusive elaboration on the comparison of the dissolution of political parties in Indonesia with Germany and Slovenia. The respect for all aspects of human rights has become the obligation of every people in citizen, including respect for the political rights of citizens. In addition, citizens have the right to participate in the dynamics of government, including the possibility of the public applying for the dissolution of political parties. This legal research statute approach, comparative approach, and conceptual approach to legislation were based on primary legal materials, secondary legal materials, and non-legal materials. The study results stated that the Subjectum Litis to the dissolution of political parties was only carried out by executive relations alone; so the public cannot apply for dissolution of political parties. Thus, this may indicate that arbitrariness also reflects the existence of particular political interests that dominate the executive's domination and try to intervene in the juridical aspect. Therefore, the researcher provides recommendations for reconstructing political subjects through various schemes; who can expand the applicant in the process of political dissolution, the applicant in the dissolution of a political party is only extended to all Indonesian people not for their official or position, and the applicant for political dissolution is carried out by the legislative and executive institutions as is practiced in Germany and Slovenia.